The interaction estimation of piles bored in sand/Centriškai apkrautų gręžtinių polų sąveikos vertinimas - Sližytė, Danute (Journal of Civil Engineering and Management, 2001)
Usually a pile foundation consists of a pile group. The difference between the behaviour of a single pile and pile group is described by H. Poulos [5] using the coefficient of interaction, which indicates the pile influence on the increasing neighbouring pile settlement, when neighbouring pile is affected by an axial load. The pile group physical modelling in centrifuge showed that really a value of the interaction coefficient is smaller than that of estimated by the existing methods. Furthemore the existing methods do not evaluate a load, roughness of lateral surface of pile and shear modulus variation with pile normalised settlement s/D. Also they do not evaluate a pile settlement restriction at a depth L. Therefore it is very important to find the calculating method for estimating the influence between piles. The article shows how the interaction coefficient can be found using theory of elasticity and experimental data of single pile.Article in Lithuanian.First Published Online: 30 Jul 2012